2022
DOI: 10.1002/ppp3.10315
|View full text |Cite
|
Sign up to set email alerts
|

(Poly)phenols of apples contribute to in vitro antidiabetic properties: Assessment of Canada's Apple Biodiversity Collection

Abstract: Apples are affordable and accessible fruit with tremendous biodiversity. Among over 10,000 identified apple cultivars, only a few are commercially available. Habitual fruit consumption is correlated with the prevention of Type 2 diabetes and related complications. Particularly, (poly)phenols found in apples are major contributors to their antidiabetic properties. Here, we have screened (poly)phenol-rich extracts of 476 apple accessions in Canada's Apple Biodiversity Collection for antidiabetic properties.The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…Thus, based on the evidence in the literature, the therapeutic dose was set at 1200 mg total apple (poly)phenol/day/human in this work, translating to 6.2 mg gallic acid equivalence (GAE)/mouse/day at the diet dose of 0.15% apple (poly)phenol. The in vitro anti-diabetic properties of (poly)phenol-rich ‘Daux Belan’ (DB) apples have been demonstrated in our previous work 7 . Therefore, in this study, the effect of DB whole apple powder supplementation on glucose and lipid homeostasis was investigated using a diet-induced obese and glucose-intolerant mouse model.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, based on the evidence in the literature, the therapeutic dose was set at 1200 mg total apple (poly)phenol/day/human in this work, translating to 6.2 mg gallic acid equivalence (GAE)/mouse/day at the diet dose of 0.15% apple (poly)phenol. The in vitro anti-diabetic properties of (poly)phenol-rich ‘Daux Belan’ (DB) apples have been demonstrated in our previous work 7 . Therefore, in this study, the effect of DB whole apple powder supplementation on glucose and lipid homeostasis was investigated using a diet-induced obese and glucose-intolerant mouse model.…”
Section: Introductionmentioning
confidence: 81%
“…It is also a good source of dietary (poly)phenols 5 . In vitro blood glucose lowering action by apple (poly)phenols is well-documented, particularly in inhibiting carbohydrate-hydrolyzing enzymes, such as α-glucosidase and α-amylase enzymes 6 , 7 , that metabolize polysaccharides into glucose as well as inhibiting glucose transporter proteins that facilitate glucose uptake, such as SGLT-1 and GLUTs 8 . In various strains of mice and rats, apple (poly)phenols improved high fat (HF)-induced body weight gain 9 , 10 , blood glucose dysregulation 10 , 11 , and hyperlipidemia 9 .…”
Section: Introductionmentioning
confidence: 99%
“…74,75 In vitro-glucosidase activity showed that procyanidin B2 could be used to reduce blood glucose levels. 76 Whereas, in the a-glucosidase inhibitory assay, it has been found that catechin has possessed signicant antidiabetic activity (IC 50 = 87.55 ± 2.23 mg mL −1 ). 77 We annotated quinic acid from F. semicordata and F. lacor with a protonated ion at m/z 193.0705 which was similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hummer et al (2023) evaluated 284 strawberry (Fragaria x ananassa) accessions for 16 traits across 2 years, generating data which quantify the enormous phenotypic variation across strawberries, as well as providing important insights for plant breeders, producers, and geneticists. Yu et al (2023) also examine a diversity collection, in this instance for apple, where they screen accessions for (poly)phenols, which were subsequently assessed for in vitro antidiabetic properties. While apples high in total (poly)phenol content may be too bitter for fresh consumption, they could be used as value‐added functional food ingredients or nutraceuticals, emphasizing the wide range of benefits and potential opportunities for fruit (Yu et al, 2023).…”
Section: How To Measure a Fruitmentioning
confidence: 99%
“…Yu et al (2023) also examine a diversity collection, in this instance for apple, where they screen accessions for (poly)phenols, which were subsequently assessed for in vitro antidiabetic properties. While apples high in total (poly)phenol content may be too bitter for fresh consumption, they could be used as value‐added functional food ingredients or nutraceuticals, emphasizing the wide range of benefits and potential opportunities for fruit (Yu et al, 2023).…”
Section: How To Measure a Fruitmentioning
confidence: 99%